2007
DOI: 10.1017/s0266462307070390
|View full text |Cite
|
Sign up to set email alerts
|

Review of a decision by the Medical Services Advisory Committee based on health technology assessment of an emerging technology: The case for remotely assisted radical prostatectomy

Abstract: This case study of LRARP demonstrates that there is sufficient crude evidence to show that this new procedure is likely to be superior to the existing procedure in terms of safety, effectiveness, and cost-effectiveness. The decision to allow MBS funding was correct and will allow for the collection of additional evidence, on both economic and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…Of these, full economic evaluation (i.e. cost-effectiveness, cost-minimisation, cost-utility, cost-benefit analysis) was performed in only six (13 %) [11][12][13][14][15][16]; the remaining articles reported cost analysis. Of note is that in many of these studies effectiveness data were also reported in the same article but these data were not interpreted along with the cost data as they would be in a full economic evaluation.…”
Section: Summary Of Search and Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, full economic evaluation (i.e. cost-effectiveness, cost-minimisation, cost-utility, cost-benefit analysis) was performed in only six (13 %) [11][12][13][14][15][16]; the remaining articles reported cost analysis. Of note is that in many of these studies effectiveness data were also reported in the same article but these data were not interpreted along with the cost data as they would be in a full economic evaluation.…”
Section: Summary Of Search and Characteristics Of Included Studiesmentioning
confidence: 99%
“…Of the 47 studies, 34 (72 %) were conducted in USA , two each in Switzerland (4 %) [51,52], Canada (4 %) [15,53], Ireland (4 %) [14,16] and Australia (4 %) [13,54], and one each in Denmark (2 %) [12], Italy (2 %) [55], Spain (2 %) [56], Sweden (2 %) [57] and the UK (2 %) [11].…”
Section: Summary Of Search and Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies were in breast cancer (publication dates 1997 to 2003) (14)(15)(16), seven were in colorectal cancer (publication dates 2000 to 2011) (17)(18)(19)(20)(21)(22)(23) and seven were in prostate cancer (publication dates 2000 to 2012) (24)(25)(26)(27)(28)(29)(30). Two of the three breast cancer studies were set in the United States (14;16), and one was in Norway (15).…”
Section: Resultsmentioning
confidence: 99%